Maternal and child factors associated with the health-promoting behaviours of mothers of children with a developmental disability. (November 2021) - Bourke-Taylor, Helen M.; Joyce, Kahli S.; Morgan, Prue; Reddihough, Dinah S.; Tirlea, Loredana
Highlights: More than half of mothers experienced mental health issues. Mothers were less satisfied with community services supporting health and wellbeing. Mothers participated in health promoting activities with low frequency. Maternal depressive symptoms predicted health promoting activity. An opportunity exists for allied health to coach/promote healthy behavior for mothers. Abstract: Background/aim: Mothers caring for their child or adult with a developmental disability can experience mental health disparity. Protective factors such as healthy behaviours are under-researched. This study investigated relationships between mental health, healthy behaviours, and disability factors. Methods: The cross-sectional online survey included: Depression Anxiety Stress Scales (DASS); Family Empowerment Scale (FES); Health Promoting Activities Scale (HPAS); and a measure of childhood quality of life (QoL). Results: All mothers were raising offspring (aged 3–36 years) with a developmental disability. Fifty-two percent of mothers (N = 81) had a mental health diagnosis. DASS scores were elevated for depression (58 %), anxiety (52 %) and stress (68 %). Mothers participated in health promoting activities infrequently and reported low satisfaction with community health-supporting facilities. Depressive symptoms, maternal empowerment and two indicators of child-related QoL explained 29.7 % of the variance in healthy behaviours. Depressive symptoms were the most important predictor of lack of health promoting behaviours. Conclusions: Better mental health predicted more frequent participation in health promoting behaviour. Future research might explore the extent to which health promoting behaviours protect mental health. Service changes including family health focused services, and custom designed health promotion or coaching programs may improve the health behaviours of mothers with high care responsibilities.